2011
DOI: 10.1189/jlb.1110602
|View full text |Cite
|
Sign up to set email alerts
|

Improved host defense against septic peritonitis in mice lacking MyD88 and TRIF is linked to a normal interferon response

Abstract: The signaling adapters MyD88 and TRIF are engaged by TLRs and/or receptors of the IL-1 family and are considered important for innate immune responses that combat bacterial infections. Here, the consequences of a combined MyD88 and TRIF deficiency for the innate immune response against severe septic peritonitis was examined. We demonstrate that Myd88 Ϫ/Ϫ ;Trif Lps2/Lps2

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
24
0
3

Year Published

2012
2012
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(32 citation statements)
references
References 55 publications
5
24
0
3
Order By: Relevance
“…We have shown here that classical NOD ligands have limited capacity to induce miR-155 in macrophages; however, the T4SS-dependent miR-155 up-regulation during infection was independent of NOD1/2 receptor activity, as demonstrated by the use here of MyD88/Trif/Rip2 −/− BMMs. The MyD88/Trif-independent up-regulation of miR-155 observed here displays a phenotype similar to that seen with the induction of TNF-α and type I IFNs or IFN-induced genes, such as CXCL10, demonstrated for intestinal bacteria-infected BMMs (60,61). IFN-β and TNF-α incubation induced miR-155 expression; however, induction of miR-155 by TLR ligands still occurred in the absence of TNF receptors and IFN-α receptors in BMMs (39).…”
Section: Discussionmentioning
confidence: 51%
“…We have shown here that classical NOD ligands have limited capacity to induce miR-155 in macrophages; however, the T4SS-dependent miR-155 up-regulation during infection was independent of NOD1/2 receptor activity, as demonstrated by the use here of MyD88/Trif/Rip2 −/− BMMs. The MyD88/Trif-independent up-regulation of miR-155 observed here displays a phenotype similar to that seen with the induction of TNF-α and type I IFNs or IFN-induced genes, such as CXCL10, demonstrated for intestinal bacteria-infected BMMs (60,61). IFN-β and TNF-α incubation induced miR-155 expression; however, induction of miR-155 by TLR ligands still occurred in the absence of TNF receptors and IFN-α receptors in BMMs (39).…”
Section: Discussionmentioning
confidence: 51%
“…We have previously demonstrated that TLR2, TLR4 and TLR9 play a deleterious role in polymicrobial sepsis [6][8]. However, the beneficial or deleterious role of the adaptor protein MyD88, recruited by these TLRs, to the outcome of polymicrobial sepsis still remains controversial [9][13].…”
Section: Introductionmentioning
confidence: 99%
“…It is generally thought that very high concentrations of cytokines in the blood late in the course of sepsis contribute to septic shock and are associated with a poor outcome. However, early production of key cytokines can enhance clearance of bacteria and survival in animal models [19,21]. The present study indicated that SMD decreased production of several pro-inflammatory cytokines and chemokines and increased production of IL-10 early in the course of sepsis.…”
Section: Discussionmentioning
confidence: 54%